(untitled) (Revista LIDER, 2021)
The objective is incorporation of gender perspective to the urban planning in contexts of periphery, and the utility of qualitative instruments for the generation of knowledge on the local thing toward an integral, inclusive and democratic politics. This work thinks about, for the analysis of local cases - GSMT -, from the qualitative methodology; looking for to identify the demands regarding to gender, to pick up people’s experience toward the reconstruction of the events, as of the actor’s point of view in the built meanings socially. The public politicians don’t incorporate gender questions, in spite of their origin or adhesion to international limits and the internationalization of this perspective. The practice demonstrates that if they are not conceived political public from this perspective; from the rescue of the knowledge of all groups; the democracy objectives and inclusion won’t be completed. This work, although it is centered in the women, doesn’t go away from the conception of the gender like category analytic that implies the inclusion of men and women in one project transformer.